1979
DOI: 10.1111/j.1439-0329.1979.tb00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß niedriger SO2-Konzentrationen auf die Aktivität einiger Glykosidasen der Assimilationsorgane verklonter Waldbäume

Abstract: 6 Kerstin FlodinHiNTiKKA, V., 1970: Selective effect on wood-decomposing Hymenomycetes. Karstenia 11, 28-32. HiiTTERMANN, A.; GEBAUER, M.; VOLGER, C; ROSGER, C., 1977: Polymerisation und Abbau von Natrium-Ligninsulfonat durch Fomes annosus (Fr.) Cooke. Holzforschung31, 84-89. JOHANSSON, M.; HAGERBY, E., 1974: Influence of growth conditions, metabolic inhibitors and phenolic compounds on the ATP pool in Fomes annosus. Physiol. Plant. 32, 23-32. JOHANSSON, M.; POPOFF, T; THEANDER, O., 1976: Effect of spruce r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…When BUCHER-WALLIN et al (1979) exposed spruce cuttings for 6 weeks in November to 290 /xg SO2-m~' they found no changes in the activities of the enzymes a-galactosidase and a-mannosidase. On the stand Kleiner Feldberg both enzymes showed less activities in current-year needles of trees of damage class 3 than in those of damage class 0.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…When BUCHER-WALLIN et al (1979) exposed spruce cuttings for 6 weeks in November to 290 /xg SO2-m~' they found no changes in the activities of the enzymes a-galactosidase and a-mannosidase. On the stand Kleiner Feldberg both enzymes showed less activities in current-year needles of trees of damage class 3 than in those of damage class 0.…”
Section: Discussionmentioning
confidence: 93%
“…a-D-Galactosidase (EC 3.2.1.22) •was estimated at pH 5.5 according to BUCHER-WALLIN et al (1979) and enzyme activities were calculated for moles of nitrophenolate produced per second and grams of needle dry weight [kat (g DW)~'] taking a molar extinction coefficient of E4oo=2OO4 [1 (mol mm)"'].…”
Section: Determination Of Enzyme Activitiesmentioning
confidence: 99%
See 3 more Smart Citations